Association of oral contraceptives and risk of endometrial cancer: A systematic review and meta‐analysis - András Harajka; Tímea Hercsik; Isabel Pinto Amorim dasVirgens; Izabella Máthé; Zsófia Tornyossy; Ali AlFarwi; Fanni Adél Meznerics; Szilvia Kiss‐Dala; Péter Fehérvári; Rita Nagy; Ferenc Bánhidy; Attila Majoros; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Although the relationship between the use of oral contraceptives and reduced endometrial cancer risk has now long been established, the need for female patients to be informed on this matter based on the latest results of scientific research remains. To help the evidence‐based decision‐making of women when choosing contraception methods, we aimed to provide them with an up‐to‐date overview and summary of past and recent findings on the association between the use of oral contraceptives and endometrial cancer risk. Material and Methods This study was registered in PROSPERO: CRD42022379871. PubMed, Embase, and Cochrane Library databases were searched on the December 5, 2022, to identify eligible articles. We included all experimental and observational studies that reported the number of users and non‐users of oral contraceptives among patients diagnosed or not with endometrial cancer. Data were extracted, and random‐effects meta‐analysis was performed to obtain summary odds ratios (OR) with 95% confidence intervals (CI). Heterogeneity across studies was assessed using Higgins & Thompson's I2 statistic. Results Fifty‐six studies were eligible for qualitative synthesis, of which twenty‐five were eligible for quantitative analysis. The use of oral contraceptives was inversely associated with the odds of having endometrial cancer (OR = 0.61, CI: 0.46–0.80). The long‐term use of oral contraceptives led to the greatest odds reduction in having endometrial cancer (≥10 years: OR = 0.31, CI: 0.13–0.70), while shorter periods were also associated with a significant decrease in these odds, although to a lesser extent (≥5 years: OR = 0.39, CI: 0.23–0.64; <5 years: OR = 0.66, CI: 0.48–0.91). Conclusions The administration of oral contraceptives is time dependently associated with lower odds of having endometrial cancer, suggesting a protective association between the use of oral contraceptives and endometrial cancer.